Semi-Standard Tableaux of Young Between Algebra and Computer Programming - Ammar Mahmood; Ayad Abdul Qader; Yahya Ibrahim (College of Education for Pure Sciences, 2006)
Since the representation theory start, the mathematics science especially in algebra began to open many new researches such our this one, we start from Schur algebra in his new representation described by Green [6], passing through his relation with semi-standard tableaux according to Green. The number of these tableaux still unknown, so we tried hardly to find the mathematical rule for this problem, but as these tableaux become great, the counting of them become difficult. Therefore, we tried to write an algorithm and a program to do so. As a result, we find the appropriate mathematical rule.